2009
DOI: 10.1007/s00787-009-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive coping and childhood anxiety disorders

Abstract: To investigate differences in cognitive coping strategies between anxiety-disordered and non-anxious 9-11-year-old children. Additionally, differences in cognitive coping between specific anxiety disorders were examined. A clinical sample of 131 anxiety-disordered children and a general population sample of 452 non-anxious children were gathered. All children filled out the child version of the Cognitive Emotion Regulation Questionnaire (CERQ-k). Structured clinical interviews were used to assess childhood anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 22 publications
(48 reference statements)
5
47
0
1
Order By: Relevance
“…Examples include reports of negative self-statements and states of mind [17], self-focused attention and negative review of past events in social anxiety [18][19][20], thought-listed worry episodes [21], and coping strategies [22]. Such reports obviously involve a high degree of conscious awareness, and, like all self-reports, are subject to social desirability and other reporting biases.…”
Section: Cognitive Content Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include reports of negative self-statements and states of mind [17], self-focused attention and negative review of past events in social anxiety [18][19][20], thought-listed worry episodes [21], and coping strategies [22]. Such reports obviously involve a high degree of conscious awareness, and, like all self-reports, are subject to social desirability and other reporting biases.…”
Section: Cognitive Content Measuresmentioning
confidence: 99%
“…In other words, anxiety can interfere with some aspects of cognition, but cognitive deficits can also contribute to anxiety. Anxiety has been found to interfere with positive reappraisals that children need to cope with negative emotion [15,22]. High levels of anxiety can also impair overall cognitive performance, though mild levels of anxiety are motivating and can enhance cognitive performance [30].…”
Section: De Cits and Strengthsmentioning
confidence: 99%
“…The questionnaire is easy to use and has good factorial validity and high reliabilities in clinical and non-clinical samples (33,34). The Persian version of CERS was provided and validated by Hasani in 2010 (35).…”
Section: The Cognitive Emotion Regulation Questionnaire (Cerq)mentioning
confidence: 99%
“…Keough et al findings (2015) indicated that people with high social anxiety use emotion-focused coping style to reduce their anxiety. Apparently, people with anxiety disorders compared to normal people are more likely to think about their feelings about negative events and less concerned how to control those events (Legerstee, Garnefski, Jellesma, Verhulst, & Utens, 2009). …”
Section: Discussionmentioning
confidence: 99%